2015
DOI: 10.1155/2015/578676
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Micropropagation Protocol byEx VitroRooting ofPassiflora edulisSims. f.flavicarpaDeg. through Nodal Segment Culture

Abstract: A procedure for rapid clonal propagation of Passiflora edulis Sims. f. flavicarpa Deg. (Passifloraceae) has been developed in this study. Nodal explants were sterilized with 0.1% HgCl2 and inoculated on Murashige and Skoog (MS) basal medium. The addition of 2.0 mgL−1 6-benzylaminopurine (BAP) to MS medium caused an extensive proliferation of multiple shoots (8.21 ± 1.13) primordial from the nodal meristems. Subculturing of these multiple shoots on the MS medium augmented with 1.0 mgL−1 of each BAP and Kinetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although acclimatization is a very sensitive stage in in vitro culture of plants, in some passion fruit genotypes, this stage has been successfully carried out (Isutsa, 2004;Shekhawat et al, 2015). According to Tanno and Biasi (2013), grapevines were efficiently acclimatized in MS medium with increasing doses of sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Although acclimatization is a very sensitive stage in in vitro culture of plants, in some passion fruit genotypes, this stage has been successfully carried out (Isutsa, 2004;Shekhawat et al, 2015). According to Tanno and Biasi (2013), grapevines were efficiently acclimatized in MS medium with increasing doses of sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Of the different concentrations of IBA tested, the maximum frequency of root formation (84%), number of roots (5.7 ± 0.41) and root length (4.4 ± 0.39 cm) was achieved in 200 µM IBA (Table 3). Ex vitro rooting was also found to be effective in Tylophora indica [9], Cyamopsis tetragonoloba [1], Cassia angustifolia [24], Passiflora edulis [23]. The advantage of this method is that rooting and acclimatization was done simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…For shoot formation from thin cell layer explants of P. edulis, 1.0 mg L -1 BA was suggested in the study by Nhut et al (2007). Jafari et al (2017) reported that the combination of 1.5 mg L -1 BAP and 0.15 mg L -1 IBA promoted the highest regeneration frequency with the highest number of shoots from cotyledonary node and shoot tip explants of P. caerulea, while semi-solid MS medium supplemented with 2.0 mg L -1 BAP was found to be most appropriate for shoot formation from nodal shoot meristems of P. foetida (Shekhawat et al, 2015 a).…”
Section: Discussionmentioning
confidence: 99%
“…Because of these problems, it is important to find the most efficient way to propagate P. edulis through in vitro culture for the micropropagation of true-to-type plant regenerants from elite plants. In vitro micropropagation of the Passifloraceae family has been reported for some species such as Passiflora alata (Pinto et al, 2010), P. caerulea (Jafari et al, 2017) and P. foetida (Shekhawat et al, 2015 a). In vitro regeneration of P. edulis has been obtained from internodal segments (Biasi et al, 2000), leaf segments (Trevisan, Mendes, 2005), hypocotyl explants (Fernando et al, 2007), apical meristem (Prammanee et al, 2011) androot (da Silva et al, 2011) and nodal (Shekhawat et al, 2015 b) segments.…”
Section: Introductionmentioning
confidence: 99%